Self-rating level of perceived exertion for guiding exercise intensity during a 12-week cardiac rehabilitation programme and the influence of heart rate reducing medication. Issue 8 (August 2016) - Tang, Lars H.; Zwisler, Ann-Dorthe; Taylor, Rod S.; Doherty, Patrick; Zangger, Graziella; Berg, Selina K.; Langberg, Henning
Abstract: Objectives: To investigate whether self-rating level of perceived exertion can adequately guide exercise intensity during a 12-week cardiac rehabilitation programme. Design: Linear regression analysis using rehabilitation data from two randomised controlled trials. Methods: Patients undergoing radiofrequency ablation for atrial fibrillation or following heart valve surgery and participating in exercise-based rehabilitation were included. The 12-week rehabilitation outpatient programme comprised three weekly training sessions, each consisting of 20 min aerobic exercise divided into three steps. Patients were asked to base their exercise intensity for each step on a predefined rating of perceived exertion specified in a training diary. Exercise intensity was objectively measured by heart rate during the last 2 min for each exercise step. Comparative analysis and linear regression of the rating of perceived exertion and heart rate were performed. Results: A total of 2622 ratings of perceived exertion were collected from 874 training sessions in 97 patients. Heart rate and rating of perceived exertion were associated both across all three exercise steps and individually for each step, with a mean of 6 to7 bpm per 1-point difference in the rating of perceived exertion ( p < 0.001). Adjusting for rate-reducing medication slightly improved the strength of the association. Conclusions: The association between change in the rating of perceived exertion and change in heart rate indicates that a diary-led and self-regulated model using rating of perceived exertion can help guide exercise intensity in everyday clinical practice among patients with heart disease, irrespective if they are taking heart rate-reducing medication.